Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1111/1468-2257.00223
|View full text |Cite
|
Sign up to set email alerts
|

Some Micro‐Evidence on the “Porter Hypothesis” from Austrian VOC Emission Standards

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 13 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Using macroeconomic data, Nemet and Kamen (2007) find little evidence of crowding out from federal energy R&D spending. However, in a survey of Austrian firms, Roediger-Schluga (2003) finds most firms cancelled or postponed other R&D projects in order to increase environmental R&D after passage of new volatile organic compound standards. 1 This paper addresses the crowding out issue directly, focusing on both the private and social opportunity costs of climate R&D. Here, the key question is whether increases in energy R&D are likely to represent new R&D spending, or whether some (or all) of the additional climate R&D comes at the expense of, or crowds out, other R&D. To address the social opportunity costs of climate R&D, we ask whether the social value of energy R&D differs from other types of innovation.…”
mentioning
confidence: 99%
“…Using macroeconomic data, Nemet and Kamen (2007) find little evidence of crowding out from federal energy R&D spending. However, in a survey of Austrian firms, Roediger-Schluga (2003) finds most firms cancelled or postponed other R&D projects in order to increase environmental R&D after passage of new volatile organic compound standards. 1 This paper addresses the crowding out issue directly, focusing on both the private and social opportunity costs of climate R&D. Here, the key question is whether increases in energy R&D are likely to represent new R&D spending, or whether some (or all) of the additional climate R&D comes at the expense of, or crowds out, other R&D. To address the social opportunity costs of climate R&D, we ask whether the social value of energy R&D differs from other types of innovation.…”
mentioning
confidence: 99%
“…Wossink and Wefering (2003) Summarizing, Ayres (1994) and Roediger-Schluga (2003) use firm level case studies as Porter and van der Linde do and find indeed 'some cases' as claimed by PL that have increases in competitiveness as perceived by firms. As PL had made a claim only on 'some cases' it should be clear that indeed they themselves found some cases for enhanced profitability, Roediger-Schluga (2003) found some cases of enhanced perceived competitiveness. Berman and Bui (2001) and Alpay et al (2002) found cases of enhanced productivity.…”
Section: Distance Functions Cum Regressionmentioning
confidence: 95%
“…On a macro level, Nemet and Kammen (2007) find little evidence of crowding out from public energy R&D spending. However, on a firm level of Austria, Roediger-Schluga (2003) found that most firm's re-schedule R&D projects in order to increase environmental R&D after passage of new volatile organic compound standards.…”
Section: Crowding Out Effects From Public Randd Spendingmentioning
confidence: 99%